miRNAs Are Involved in Determining the Improved Vigor of Autotetrapoid Chrysanthemum nankingense - Dong, Bin; Wang, Haibin; Song, Aiping; Liu, Tao; Chen, Yun; Fang, Weimin; Chen, Sumei; Chen, Fadi; Guan, Zhiyong; Jiang, Jiafu (Frontiers in Plant Science, 2016)
Many plant species are autopolyploid, a condition frequently associated with improvements in both vegetative and reproductive vigor. The possible contribution of miRNAs to this improvement was investigated by characterizing the miRNA content of a diploid and an autotetraploid form of Chrysanthemum nankingense. 162 and 161 known miRNA sequences were identified in 2x and 4x library. The length of 22 and 25 nt was predominant in diploid. However, 21 and 24 nt showed dominance in autotetraploid. It seems likely that autopolyploidization have had an immediate effect the distribution of miRNAs. In addition, the abundance of the miRNAs differed markedly between the two ploidy levels and contributed to their targets diversity. A number of target genes associated with miRNAs play important roles in growth and development. The conclusion was that some miRNAs likely make a contribution to the vigor displayed by autotetraploid C. nankingense.